Continuous generation of delayed light. (23rd October 2017) - Smartsev, Slava; Eger, David; Davidson, Nir; Firstenberg, Ofer
Abstract: We use a four-wave mixing process to read-out light from atomic coherence which is continuously written. The light is continuously generated after an effective delay, allowing the atomic coherence to evolve during the process. Contrary to slow-light delay, which depends on the medium optical depth, here the generation delay is determined solely by the intensive properties of the system, approaching the atomic coherence lifetime at the weak driving limit. The atomic evolution during the generation delay is further manifested in the spatial profile of the generated light due to atomic diffusion. Continuous generation of light with a long intrinsic delay can replace discrete write–read procedures when the atomic evolution is the subject of interest.